2019
DOI: 10.1101/688572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time spent in distinct life-history stages has sex-specific effects on reproductive fitness in wild Atlantic salmon

Abstract: the fitness advantage of later sea age maturation. Our results show that the timing of transitions between juvenile and adult phases has a sex-specific consequence on female reproductive fitness, demonstrating a lifehistory trade-off between maturation and reproduction in wild Atlantic salmon.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Given that larger size at a given sea age is indicative of higher performance and fitness in adult salmon (e.g. Fleming, 1996; Mobley et al., 2020), the six6 * L allele (being linked to larger size) may be expected to have a selective advantage over the E allele and is hence predicted to prevail within and among populations as a result of directional selection. However, the six6 genomic region is highly variable within and among populations (Barson et al., 2015; Pritchard et al., 2018), and balancing selection appears to be the pervasive mode of evolution, with both alleles exerting fitness advantage with different life‐history strategies (Barson et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given that larger size at a given sea age is indicative of higher performance and fitness in adult salmon (e.g. Fleming, 1996; Mobley et al., 2020), the six6 * L allele (being linked to larger size) may be expected to have a selective advantage over the E allele and is hence predicted to prevail within and among populations as a result of directional selection. However, the six6 genomic region is highly variable within and among populations (Barson et al., 2015; Pritchard et al., 2018), and balancing selection appears to be the pervasive mode of evolution, with both alleles exerting fitness advantage with different life‐history strategies (Barson et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the strength and direction of selection on size was sometimes dependent on sex and year (Table 4 ; Kodama et al, 2012 ). Age, which is generally correlated with size, also demonstrated a positive relationship with LRS in some studies (Mobley et al, 2019 , 2020 ), but the results were sex‐specific in another study which demonstrated a positive relationship in males, but a more complex relationship in females (Christie et al, 2018 ).…”
Section: Effects Of Life History and Phenotypic Variation On Lifetime Reproductive Successmentioning
confidence: 96%
“…Life‐history traits such as adult migration timing and duration spent in freshwater versus ocean are often variable within salmonid populations (Quinn et al, 2016 ) but have also largely been unaccounted for in studies of LRS with only a few recent exceptions (Ford et al, 2016 ; Janowitz‐Koch et al, 2019 ; Mobley et al, 2020 ). Given that genes of major effect have been shown to drive phenotypic variation for these traits across species of salmonids (Barson et al, 2015 ; Prince et al, 2017 ; Waters et al, 2021 ), accounting for trait variation can substantially influence estimates of LRS within populations.…”
Section: Caveats Future Directions and Conservation Implicationsmentioning
confidence: 99%
“…Substantial variation in Atlantic salmon sea age at maturity is maintained due to a trade-off between mating success at spawning grounds and survival, whereby individuals that mature later are larger and have higher reproductive success on the spawning grounds, but lower survival and thus lower chance of reaching reproductive age. In contrast individuals that mature early are smaller and have lower reproductive success, but higher survival and thus higher chance of reaching reproductive age [27,28].…”
Section: Introductionmentioning
confidence: 99%